Is Ataxia an Underestimated Symptom of Huntington's Disease? - Franklin, Gustavo L.; Camargo, Carlos Henrique F.; Meira, Alex T.; Pavanelli, Giovana M.; Milano, Sibele S.; Germiniani, Francisco B.; Lima, Nayra S. C.; Raskin, Salmo; Barsottini, Orlando Graziani Povoas; Pedroso, José Luiz; Maggi, Fernanda Aparecida; Tumas, Vitor; et al. (Frontiers in Neurology, 2020)
Background: Huntington’s disease (HD) is a progressive disorder characterized by motor, cognitive and psychiatric features. Cerebellar ataxia is classically considered as uncommon in HD clinical spectrum. Objective: To determine the prevalence of cerebellar ataxia in patients with HD, both in the early and in the late stages of HD. Methods: Seventy-two individuals considered eligible were assessed by two trained doctors, applying the Scale for Assessment and Rating of Ataxia (SARA) and Brief Ataxia Rating Scale (BARS) for ataxia, the Unified Huntington's Disease Rating Scale (UHDRS) and also, Barthel Index (BI), in order to evaluate functional capacity. Results: Fifty-one patients (70.8%) presented with clinical ataxia at the time of examination (mean time of disease was 9.1 years). Six (8.33%) patients presented with cerebellar ataxia as first symptom. When stratified according to time of disease, a decline in the presence of chorea (p = 0.032) and an increase in cognitive deficit (p = 0.023) were observed in the patients as the disease progressed. The presence of ataxia was associated with longer duration of illness and severity of illness (UHDRS) (p < 0.0001), and shorter Barthel (less functionality) (p = 0.001). Conclusions: Cerebellar involvement may play an important role in natural history of brain degeneration in HD. The presence of cerebellar ataxia in HD is relevant and it may occur even in early stages, and should be included as part of the motor features of the disease.